Foliar Application of Micronutrients on the Morpho-agronomic Characterization and Fruit Quality in Papaya (Carica papaya L.) Cv. Red Lady - Prakasha , D. P.; Preethi, M. (International Journal of Bio-resource and Stress Management, 2025)
The present study was conducted during April, 2023 to March, 2024 at farmers field adjoining to College of Horticulture, Sirsi (Location), Karnataka, India to evaluate the effect of micronutrients, time / period, frequency and concentration of foliar application of micronutrient mixture (iron, boron and zinc) on plant growth, yield and fruit quality in papaya Cv. Red Lady. Results indicated that the time of foliar application of micronutrients was highly significant on all reproductive, yield and quality traits recorded. The treatment with foliar spray at 1, 3, 5, 7 months was the best as it recorded reduced number of days taken for flower initiation, increased number of flowers, number of fruits set, fruit weight, yield, TSS and shelf life of fruits and vary less percent of deformed fruits (13.12 days, 25.62%, 41.65%, 36.28%, 91.82%, 21.69%, 45.45% and 3.39%, respectively), which indicated continues supply of micronutrients is favorable for both increased yield and quality of fruits. In another experiment the frequency and concentration of foliar application of micronutrient significant influence on most of reproductive parameters. Further, yield parameters (weight of fruit, length, cavity diameter, fruit plant-1 and hectare) (highest of the was1.52 kg, 24.50cm, 46.08 kg and 144.13 t ha-1, respectively) and quality parameters were also significantly influenced and the highest of them was noticed in with spraying fruit special containing (at 5 g l-1) at 30 days interval. In conclusion, extended application of micronutrients up to eight month was useful for improved yield and quality parameters in papaya cv. Red lady.